Exploring the Link between Micronutrients and Phytoplankton in the Southern Ocean during the 2007 Austral Summer - Hassler, Christel; Sinoir, Marie; Clementson, Lesley; Butler, Edward C. (Frontiers in Microbiology, 2012)
Bottle assays and large-scale fertilisation experiments have demonstrated that, in the Southern Ocean, iron often controls the biomass and the biodiversity of primary producers. To grow, phytoplankton need numerous other trace metals (micronutrients) required for the activity of key enzymes and other intracellular functions. However, little is known of the potential these other trace elements have to limit the growth of phytoplankton in the Southern Ocean. This study investigates the link between the distribution of several micronutrients (Zn, Co, Cu, Cd, Ni) and phytoplankton from samples collected during the SAZ-Sense oceanographic expedition (RV Aurora Australis, Jan.–Feb. 2007). Larger phytoplankton are usually associated with lower diffusive supply and higher micronutrient requirement; for this reason, the delineation between phytoplankton larger than 10 µm and those with a size ranging from 0.8–10 µm was made. In addition, different species of phytoplankton may have different requirements to sustain their growth; the phytoplankton biodiversity here was inferred using biomarker pigments. This study, therefore, attempts to elucidate whether micronutrients other than iron need to be considered as parameters for controlling the phytoplankton growth in the Australian sector of the Southern Ocean. Understanding of the parameters controlling phytoplankton is paramount, as it affects the functioning of the Southern Ocean, its marine resources and ultimately the global carbon cycle.